Mucocutaneous manifestations in newborn: a study from tertiary care centre, Karnataka - Virupakshappa, T.; Sindhuri, K.; Takalkar, Anant A. (International Journal of Research in Dermatology, 2019)
Background: The spectrum of dermatological manifestations in neonates varies from era to era and country to country. Skin lesions in neonatal period vary from transient self-limiting conditions to serious dermatoses, requiring specific therapies. Skin lesions are extremely common in newborns and can be a significant source of parental concern. The objective of the study was to study various mucocutaneous lesions in newborn babies. Methods: The present descriptive cross sectional observational study was conducted in department of dermatology, Navodaya Medical College, Raichur. A total 500 neonates were included in the study from January 2012 to September 2013. Data collected and analysed by using SPSS 16.0 version. Results: Prevalence of skin lesions in this study was found to be 97.4%. Maximum skin lesions were observed in 47 subjects (9.4%). Prevalence of Epstein pearls was 58%, Mongolian spots 53.6% and erythema toxicum neonatorum was 28%. Epstein pearls (males 60.2%, female 55.7%) and Mongolian spots (males 53.9%, females 53.3%) predominated. Conclusions: Prevalence of mucocutaneous skin lesions in newborn babies was 97.4%. High prevalence of Epstein pearls (58%), Mongolian spots (53.6%) and erythema toxicum neonatorum (28.6%) were observed.